2020
DOI: 10.2147/opth.s271820
|View full text |Cite
|
Sign up to set email alerts
|

<p>Etiologies of Acute Optic Neuritis in Thailand: An Observational Study of 171 Patients</p>

Abstract: Purpose: To analyze the demographic patterns, clinical characteristics and etiologies of acute optic neuritis (ON). Methods: This retrospective observational study included patients with acute ON who presented to a university hospital in Bangkok, Thailand, between January 2010 and March 2020. The demographic details, clinical characteristics and etiologies of acute ON were evaluated. Results: A total of 171 patients were included in the study (78.4% [n=134] female; mean age 45 years [standard deviation 15.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…104,109,110 In recent large cohort studies applying 2017 criteria for MS, the proportion of ON associated with MS varies from 14%-28% at first diagnosis, 104,105 to 33%-57% after varied follow-up periods. [103][104][105] In Asian populations, the proportion of ON associated with MS at first diagnosis (from 2% to 16%) 54,102,111 and the conversion rate to MS after isolated ON (3%-18% after 5 years) are lower than in non-Asian populations. 100,102,[112][113][114] Other etiologies.…”
Section: Epidemiology Of On With Current Diagnosis Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…104,109,110 In recent large cohort studies applying 2017 criteria for MS, the proportion of ON associated with MS varies from 14%-28% at first diagnosis, 104,105 to 33%-57% after varied follow-up periods. [103][104][105] In Asian populations, the proportion of ON associated with MS at first diagnosis (from 2% to 16%) 54,102,111 and the conversion rate to MS after isolated ON (3%-18% after 5 years) are lower than in non-Asian populations. 100,102,[112][113][114] Other etiologies.…”
Section: Epidemiology Of On With Current Diagnosis Criteriamentioning
confidence: 99%
“…115 The proportion of CRION cases may be approximately 2%-10% of ON cases, many of them have simultaneous MOG seropositivity. 111,116,117 The proportions of other ON etiologies are lower and not well known. The few studies that counted them found less than 2%.…”
Section: Epidemiology Of On With Current Diagnosis Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“… 3 , 4 Correspondingly, idiopathic-ON is the most common etiology of ON in Thais (51.5%), followed by neuromyelitis optica spectrum disorder (NMOSD, 30.9%), autoimmune disorder (9.9%), myelin oligodendrocyte glycoprotein antibody-associated disorder (MOGAD, 5.3%), multiple sclerosis (MS, 1.8%), and postinfection (0.6%). 5 …”
Section: Introductionmentioning
confidence: 99%